Chemical Constituents, Anticancer and Anti-Proliferative Potential of Limonium Species: A Systematic Review - Naiara Cássia Gancedo; Raquel Isolani; Natalia Castelhano de Oliveira; Celso Vataru Nakamura; Daniela Cristina de Medeiros Araújo; Andreia Cristina Conegero Sanches; Fernanda Stumpf Tonin; Fernando Fernandez-Llimos; Danielly Chierrito; João Carlos Palazzo de Mello (MDPI AG, 2023)
Limonium species represent a source of bioactive compounds that have been widely used in folk medicine. This study aimed to synthesize the anticancer and anti-proliferative potential of Limonium species through a systematic review. Searches were performed in the electronic databases PubMed/MEDLINE, Scopus, and Scielo and via a manual search. In vivo or in vitro studies that evaluated the anticancer or anti-proliferative effect of at least one Limonium species were included. In total, 942 studies were identified, with 33 articles read in full and 17 studies included for qualitative synthesis. Of these, 14 (82.35%) refer to in vitro assays, one (5.88%) was in vivo, and two (11.76%) were designed as in vitro and in vivo assays. Different extracts and isolated compounds from Limonium species were evaluated through cytotoxic analysis against various cancer cells lines (especially hepatocellular carcinoma-HepG2; n = 7, 41.18%). Limonium tetragonum was the most evaluated species. The possible cellular mechanism involved in the anticancer activity of some Limonium species included the inhibition of enzymatic activities and expression of matrix metalloproteinases (MMPs), which suggested anti-metastatic effects, anti-melanogenic activity, cell proliferation inhibition pathways, and antioxidant and immunomodulatory effects. The results reinforce the potential of Limonium species as a source for the discovery and development of new potential cytotoxic and anticancer agents. However, further studies and improvements in experimental designs are needed to better demonstrate the mechanism of action of all of these compounds.